Problematika Metodologi Hukum Islam Ghairu Mahdhah di Indonesia - Muhaimin Muhaimin (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2020)
This article aims to find essays (ontologies) that are able to answer the problems of implementing the Islamic law of Ghairu Mahdhah in Indonesia. The study of this article is included in the literature review using a dialectical reasoning approach between text (naṣ) and context (empiricity) and is guided by maqasid al-sharia so that the legal product does not deviate from the essence (ontology) of Islamic law itself. The results of this study indicate that the dominance of the bayani epistemology which prioritizes text (naṣ) in understanding the sources of Islamic law and its legal products are normative-idealistic (das sollen) are very much felt in Indonesia today. Legal products of this kind are ideal (das sollen) often leave empirical-sociological dynamics and tend to give birth to exclusive, emotional and truth claims. The essence of this religious attitude is really needed, but its implementation often ignores the realities of society (das sein). AbstrakArtikel ini bertujuan untuk menemukan esesnsi (ontologi) yang mampu menjawab problematika implementasi hukum Islam Ghairu Mahdhah di Indonesia. Kajian artikel ini termasuk dalam kajian kepustakaan dengan menggunakan pendekatan nalar dialektika antara teks (naṣ) dengan konteks (empirisitas) dan dipandu dengan maqasid al-syariah agar produk hukumnya tidak menyimpang dari esensi (ontologi) hukum Islam itu sendiri. Hasil kajian ini menunjukkan bahwa dominasi epistemologi bayani yang lebih mengedepankan teks (naṣ) dalam memahami sumber hukum Islam dan produk hukumnya bersifat normatif-idealistik (das sollen) sangat dirasakan di Indonesia saat ini. Produk hukum semacam ini bersifat ideal (das sollen) seringkali meninggalkan dinamika empiris-sosiologis dan cenderung melahirkan sikap eksklusif, emosional dan truth claim. Inti sikap religius ini memang sangat dibutuhkan, namun seringkali implementasinya mengabaikan realitas masyarakat (das sein).